Enhancing Financial Capability and Inclusion in Zambia : A Demand-Side Assessment - World Bank Group (World Bank, Zambia, 2017)
Financial inclusion in Zambia has nearly doubled in the last ten years - from 21.3 percent in 2005 to 40.2 percent in 2016. This success was made possible by Zambia’s Financial Sector Development Plan that concluded in 2015. And yet, when compared to other lower-middle income countries, Zambia fares less favorably in terms of account ownership, accessibility of bank branches, and usage of financial services. Main cited barriers are lack of funds, high fees, time-consuming travel, and lack of trust in the financial sector. Zambia aims to achieve universal access and has committed to implementing comprehensive national strategies for financial inclusion and financial education to accelerate progress. The World Bank survey covered in this report was requested by Zambian authorities to inform their further strategy work, help formulate quantifiable and concrete targets, and assess the effectiveness of future financial capability enhancing programs. The key findings and recommendations of the report cover areas related to Financial Inclusion, Financial Capability, and Financial Consumer Protection, followed by four chapters. Chapter 1 explores the financial inclusion landscape in Zambia. Chapter 2 reviews financial capability of Zambians in terms of their financial knowledge, attitudes, and behaviors. Chapter 3 analyzes the link between financial inclusion and financial capability in Zambia, and Chapter 4 assesses whether the financial products in Zambia meet consumers’ needs.